EFFECTIVENESS OF TREATMENT OF MALOCCLUSION IN CHILDREN - Azimova Shakhnoza Shukhratovna (TADQIQOTLAR.UZ, 2024)
Abstract: Among dental diseases, dental anomalies in frequency and prevalence occupy the third place after dental caries and periodontal diseases. Their diagnosis and treatment is considered one of the urgent tasks in orthodontics, they affect chewing functions, cause speech disorders, aesthetic defects and limit the manifestation of human potential, significantly reducing the quality of life. This pathological condition causes various pathological changes in the temporomandibular joint, along with a violation of the cosmetic condition, a violation of chewing food. With pathological bites in adolescents, there are also changes in their general psycho-emotional state.